VISUAL BRANDING DINAS KOMUNIKASI DAN INFORMATIKA DAERAH ISTIMEWA YOGYAKARTA MELALUI KONTEN INSTAGRAM: SEBUAH TINJAUAN SEMIOTIK - Kholifatul Fauziah; Putri Bagus Aulia (Nusantara Hasana Journal, 2024)
This research aims to examine, from a semiotic perspective, the visual characteristics of the branding of the Yogyakarta Special Region Communication and Information Service (Kominfo DIY) conveyed through Instagram content. The research was conducted with a qualitative approach using Roland Barthes' semiotic model on the visual elements of Instagram content in the form of illustrations, colors, typography and layout. The Kominfo DIY Instagram content, uploaded in February 2023, is the unit of analysis for this research. Documentation of the unit of analysis and secondary data was carried out as a data collection technique. The findings show that the visual characteristics of Kominfo DIY branding through Instagram content are effective. This can be seen from the formal dynamic pattern used. This pattern can be seen in the consistency of color patterns, typography and layout. The illustrations used tend to be varied and attention-grabbing. Theoretically, these findings show a formal-dynamic pattern of visual branding in Instagram content that can be practically adopted by government organiZations to convey an official and engaging message.